Silent lesions on MRI imaging – Shifting goal posts for treatment decisions in multiple sclerosis. (October 2018) - Min, Myintzu; Spelman, Tim; Lugaresi, Alessandra; Boz, Cavit; Spitaleri, Daniele LA; Pucci, Eugenio; Grand'Maison, Francois; Granella, Franco; Izquierdo, Guillermo; Butzkueven, Helmut; Sanchez-Menoyo, Jose Luis; Barnett, Michael; et al.
Background: The current best practice suggests yearly magnetic resonance imaging (MRI) to monitor treatment response in multiple sclerosis (MS) patients. Objective: To evaluate the current practice of clinicians changing MS treatment based on subclinical new MRI lesions alone. Methods: Using MSBase, an international MS patient registry with MRI data, we analysed the probability of treatment change among patients with clinically silent new MRI lesions. Results: A total of 8311 MRI brain scans of 4232 patients were identified. Around 26.9% (336/1247) MRIs with one new T2 lesion were followed by disease-modifying therapy (DMT) change, increasing to 50.2% (129/257) with six new T2 lesions. DMT change was twice as likely with new T1 contrast enhancing compared to new T2 lesions odds ratio (OR): 2.43, 95% confidence interval (CI): 2.00–2.96 vs OR: 1.26 (95% CI: 1.22–1.29). DMT change with new MRI lesions occurred most frequently with 'injectable' DMTs. The probability of switching therapy was greater only after high-efficacy therapies became available in 2007 (after, OR: 1.43, 95% CI: 1.28–1.59 vs before, OR: 0.98, 95% CI: 0.520–1.88). Conclusion: MS clinicians rely increasingly on MRI alone in their treatment decisions, utilizing low thresholds (1 new T2 lesion) for optimizing MS therapy. This signals a shift towards no evidence of disease activity (NEDA)-3 since high-efficacy therapies became available.